Electric Sasando of East Nusa Tenggara, Indonesia - Yohanes Don Bosko Bakok (IJCAS (International Journal of Creative and Arts Studies), 2014)
Sasando is a stringed musical instrument from Rote Island, East Nusa Tenggara, Indonesia. Based on the resulting tones, this instrument consists of two types namely gong sasando that produces pentatonic tones and violin sasando that produces diatonic tones. Based on these two kinds of sasando the electric sasando has been created with the consequence that some of original characteristic of accoustic sasando had been eliminated. Up to this point, a question is raised, why the electric sasando was created and how is its history? To analyze this problem I use the popular culture studies to indicate that the creation of electric sasando is closely linked with consumer demand, that influenced by popular culture. The datas are obtained through direct observation and by interviewing the informans. Result sows that the creation of electric sasando is influenced by consumer demand who live in popular and mass culture.